Unravelling the Interfacial Dynamics of Bandgap Funneling in Bismuth-Based Halide Perovskites - Tang, Y.; Mak, C.H.; Zhang, J.; Jia, Guohua; Cheng, K.C.; Song, H.; Yuan, M.; Zhao, S.; Kai, J.J.; Colmenares, J.C.; Hsu, H.Y. (2023)
An environmentally friendly mixed-halide perovskite MA3Bi2Cl9−xIx with a bandgap funnel structure has been developed. However, the dynamic interfacial interactions of bandgap funneling in MA3Bi2Cl9−xIx perovskites in the photoelectrochemical (PEC) system remain ambiguous. In light of this, single- and mixed-halide lead-free bismuth-based hybrid perovskites—MA3Bi2Cl9−yIy and MA3Bi2I9 (named MBCl-I and MBI)—in the presence and absence of the bandgap funnel structure, respectively, are prepared. Using temperature-dependent transient photoluminescence and electrochemical voltammetric techniques, the photophysical and (photo)electrochemical phenomena of solid–solid and solid–liquid interfaces for MBCl-I and MBI halide perovskites are therefore confirmed. Concerning the mixed-halide hybrid perovskites MBCl-I with a bandgap funnel structure, stronger electronic coupling arising from an enhanced overlap of electronic wavefunctions results in more efficient exciton transport. Besides, MBCl-I's effective diffusion coefficient and electron-transfer rate demonstrate efficient heterogeneous charge transfer at the solid–liquid interface, generating improved photoelectrochemical hydrogen production. Consequently, this combination of photophysical and electrochemical techniques opens up an avenue to explore the intrinsic and interfacial properties of semiconductor materials for elucidating the correlation between material characterization and device performance.